1982
DOI: 10.1007/bf00313402
|View full text |Cite
|
Sign up to set email alerts
|

Neurological complications following rubella infection

Abstract: Neurological complications following rubella are only rarely encountered. However, in many cases severe neurological impairment may occur, leading to permanent disability. In a recent epidemic of rubella in Israel during the years 1978-1979, 20 patients with severe neurological complications have been seen. We report on 5 cases of which 3 are described in detail. Considering the efficacy of immunization against rubella, we suggest that in countries such as England and Israel in which periodic epidemics of rube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
3

Year Published

1989
1989
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 19 publications
0
9
1
3
Order By: Relevance
“…Usually, thrombocytopenic purpura (1 in 3,000 cases) and encephalitis (1 in 6,000 cases) are infrequent complications of rubella (11,12). However, the frequencies of thrombocytopenic purpura and encephalitis in our study were much higher (1 in 217 cases and 1 in 823 cases, respectively).…”
Section: Discussioncontrasting
confidence: 46%
“…Usually, thrombocytopenic purpura (1 in 3,000 cases) and encephalitis (1 in 6,000 cases) are infrequent complications of rubella (11,12). However, the frequencies of thrombocytopenic purpura and encephalitis in our study were much higher (1 in 217 cases and 1 in 823 cases, respectively).…”
Section: Discussioncontrasting
confidence: 46%
“…4). The change in morphology shows higher surface area of Mo/ZrO2 when compared to ZrO2 [35,36]. Synthesis of O-methoxymethylated compounds over 10 % Mo/ZrO2: In general a mixture of various alcohols, dimethoxymethane (1:10 mole ratio) and 0.05 g of 10 Mo/ ZrO2 was added and the mixture was refluxed at 40 °C for an appropriate time under nitrogen.…”
Section: Resultsmentioning
confidence: 99%
“…For MoO x /ZrO 2 samples with higher surface density (>5 Mo/nm 2 ), treatment in air at 723 K led to the predominant formation of MoO 3 , while higher treatment temperatures led to a solid-state reaction between MoO 3 and ZrO 2 to form Zr(MoO 4 ) 2 . Meanwhile, the effect of Mo loading on ZrO 2 in respect to the catalytic activities was reported by Chary et al [21] and Kenney et al [22]. Chary et al demonstrated the catalytic ammoxidation of toluene to benzonitrile over MoO 3 -ZrO 2 increased with loading up to 6.6 wt.% MoO 3 .…”
Section: Introductionmentioning
confidence: 89%